ANALISIS BELAJAR SISWA DARI RUMAH SELAMA MASA PANDEMI COVID-19 PADA PEMBELAJARAN MATEMATIKA KELAS II SD NEGERI 22 LUBUKLINGGAU - Gita Rama; Akmal Rijal; Riduan Febriandi (Primary Education Journal Silampari (PEJS), 2021)
This study aims to determine how the Mathematics learning process of students from home during the Covid-19 pandemic, to find out whether the obstacles faced by students learning from home and to find out what solutions are given for Class II Mathematics learning. SD Negeri 22 Lubuklinggau can be reached. The research method used is descriptive qualitative, data collection through observation, interviews, questionnaires, and documentation. The data that has been obtained are then analyzed using data reduction, data presentation and drawing conclusions. The subject of this research is the analysis of learning from home during the Covid-19 pandemic, 12 students in class II A and 12 students in class II B, with a total of 24 students. The learning process from the homes of class II students uses an online learning system with the whastapp group application, the obstacles experienced by students in learning Mathematics are difficulties in counting, writing, and doing assignments given by the teacher, other obstacles that are found are disruption of the internet network for students and teachers. It can be concluded that during the covid-19 pandemic the learning process of students from home through online learning, the teacher provides motivation before providing material, students are also asked to attend their attendance, then the teacher explains the subject matter according to the materials on the day. The obstacles faced bt students are that students cannot concentrate on learning from home because of the many disturbances from the sounds around them, children also mostly play when studying at home. As for the solution obtained by the researcher to overcome the obstacles that occur, the teacher is expected to be able to create a fun online learning method so that students do not feel bored in learning at home, the teacher can also make videos when teaching using learning media when learning Mathematics. Keywords: Analysis, Learning from Home, Class II